Training of improving Arabic learning ability through the singing method in TK Paud R.A. Madrasah Hamdariyah in Medan Tembung District - Nasution, Khairina; Lubis, Husnan; Pujiati; Takari (Talenta Publisher, 2019)
The community service that was carried out in TK PAUD R.A. Madrasah Hamdaniyah aims to improve the ability to learn Arabic through singing methods. The implementation of this service also includes improving the community's value system from the point of education. Arabic subjects have been taught in this kindergarten but the learning activities are not running optimally because the teacher still teaches Arabic using conventional methods. Another problem was found in the absence of media used to sing so that children quickly feel bored and bored when learning Arabic. To overcome this problem, the community service team at USU's Fakulty of Cultural Studies community will provide a solution to the problems found by replacing conventional methods with singing when teaching Arabic vocabulary. The method used in this service is the singing method and is supported by lecture, discussion, simulation and demonstration methods. Then the songs were sung by two students who participated in the service and were taught to kindergarten PAUD R.A. Madrasah Hamdaniyah. After dedication to kindergarten PAUD R.A. Madrasah Hamdaniyah results are very satisfying. Kindergarten children PAUD R.A. Madrasah Hamdaniyah does not feel afraid, ashamed and insecure anymore to actively participate in class. They began to dare to sing in front of the class and could answer the questions given.